A research hotspot for Microgastrinae parasitoid wasps (Hymenoptera, Braconidae) in North America: DNA barcoding reveals the need for increased taxonomic efforts in dark taxa - Beaudin, Melanie; Höcherl, Amelie; Boudreault, Caroline; Cullingham, Catherine I.; Lapen, David; Fernandez-Triana, Jose (Frontiers in Sustainable Food Systems, 2025)
Microgastrinae parasitoid wasps (Hymenoptera: Braconidae) were studied in the St. Lawrence Lowlands ecoregion ( 14,100 km2) in Ontario, Canada. This subfamily is one of (if not the) most species-rich clades of Lepidoptera parasitoids and has important applications in the biological control of agricultural pests. The St. Lawrence Lowlands ecoregion is one of the nine southern Canadian ecoregions to be identified as a “crisis ecoregion,” having high biodiversity, high risk of biodiversity loss, and low proportion of land included in protected areas. A total of 3,481 specimens collected from 1905 to 2021 within the region were studied. Two species are recorded for the first time in the Nearctic: Apanteles minornavarroi Fernandez-Triana, 2014 and Protapanteles anchisiades (Nixon, 1973); two species are recorded for the first time in Canada: Promicrogaster virginiana Fernandez-Triana, 2019 and Protapanteles immunis (Haliday, 1834); and two are recorded for the first time in Ontario: Cotesia plathypenae (Muesebeck, 1921) and Alphomelon winniewertzae Deans, 2003. DNA-barcode sequences for 2,173 specimens and 66% of the formally described species were successfully recovered. Using a combination of DNA barcodes and morphological assessment, we document herein a minimum putative species count of 228 and a maximum count of 304. We assess the accuracy of species identification in the ecoregion through DNA barcodes and discuss the use of Barcode Index Numbers (BINs) for species discovery in this taxon. Using BINs, 83% of the formally described species with molecular data can be successfully discriminated. The incredible diversity revealed by DNA-barcoding and the high risk of biodiversity loss in the ecoregion highlight the need for increased taxonomic efforts in this taxon to catalog species before they are potentially lost. Several species are present solely in unique habitats within the study area, such as Sphagnum bogs and wetlands. Other (semi) natural features important for these beneficial insects include hedgerows, riparian zones, ditch banks, and wooded areas. Enrichment of these habitats in proximity to field crops could help maintain microgastrine populations and control Lepidoptera crop pests.